Fintech Index for ASEAN-6 Countries - Alice Yong-Zheng, Huong (Universiti Malaysia Sarawak (UNIMAS), 2021)
The financial services industries are no exception to the substantial growth in the Fintech which acts as the digital economy's driver aim to improve interaction across various nations. However, the uncertainty associated with the future development of Fintech in ASEAN is considered ambiguity with a comparative little attention on investigation. Further research on the Fintech ecosytem in these countries is required to validate the future growth of Fintech in ASEAN countries. Therefore, this study constructed a composite index, namely ASEAN6 Fintech Index (AFI) from 2017 to 2019 to study the readiness and capacity to engage in Fintech activity, level of demand of Fintech services and the potential future development of Fintech in each country based upon their Fintech ecosystem at macro level promptly in a single measure. The index captures four dimensions of Fintech ecosystem which include regulation and policy, infrastructure, demand and innovative product and service. The final score of ASEAN-6 Fintech Index (AFI) is calculated based on the average result from the three aggregation methods which are arithmetic mean, geometric mean and entrophy method. From the results, Singapore is ranked the highest among the six ASEAN countries in which it implies that Singapore has the most favourable Fintech ecosystem among ASEAN-6 countries, followed by Thailand, Malaysia, Vietnam, Indonesia and Philippine during 2019. The results of this study imply that the government in Indonesia should focus on formulating effective policy to resolve its main challenge in ICT infrastructure development in order to support the Fintech development.